Basidiobolomycosis of the Colon Masquerading as Stenotic Colon Cancer - M. Ezzedien Rabie; Ismail El Hakeem; Mubarak Al-Shraim; M. Saad Al Skini; Salim Jamil (Case Reports in Surgery)
Basidiobolus ranarum is a widespread saprophyte fungus with pathogenic potential. It affects mainly the subcutaneous tissues of the trunk and limbs. Relatively recently, occasional reports of gastrointestinal basidiobolomycosis appeared in the literature. Due to the rarity of the condition and the nonspecific presenting features, the correct diagnosis is usually hard to reach. In this paper, we describe the clinical course of an otherwise healthy female, who presented with a colonic mass. She received subtotal colectomy followed by oral itraconazole, with successful outcome.